An Open–Label, Randomized, Multi–Center Study Comparing the Sequence of High Dose Aldesleukin (Interleukin–2) and Ipilimumab (Yervoy) in Patients with Metastatic Melanoma. (1st January 2021) - Hasanov, Merve; Milton, Denái R.; Sharfman, William H.; Taback, Bret; Cranmer, Lee D.; Daniels, Gregory A; Flaherty, Lawrence; Hallmeyer, Sigrun; Milhem, Mohammed; Feun, Lynn; Hauke, Ralph; Doolittle, Gary; et al.
ABSTRACT: Combination immunotherapy with sequential administration may enhance metastatic melanoma (MM) patients with long-term disease control. High Dose Aldesleukin/Recombinant Interleukin-2 (HD rIL-2) and ipilimumab (IPI) offer complementary mechanisms against MM. This phase IV study assessed the sequenced use of HD rIL-2 and IPI in MM patients. Eligible Stage IV MM patients were randomized to treatment with either two courses of HD rIL-2(600, 000 IU/kg) followed by four doses of IPI 3 mg/kg or vice-versa. The primary objective was to compare one-year overall survival (OS) with historical control (46%, Hodi et al., NEJM 2010). Secondary objectives were 1-year progression-free survival (PFS), objective response rate (ORR), and adverse events (AEs) profile. Evaluable Population (EP) included patients who received at least 50% of planned treatment with each drug. Thirteen and 16 patients were randomized to receive HD rIL-2 first, and IPI first, respectively. One-year OS rate was 75% for intention to treat population. Eighteen patients were included in EP, 8 in HD rIL-2, 10 in IPI first arm. In EP, 1-year OS, PFS and ORR rates were 87%, 68%, and 50%, respectively. The frequency of AEs was similar in both arms with 13 patients experiencing Grade 3 or higher AEs, 3 resulting in the end of study participation. There was one HD rIL-2-related death, from cerebral hemorrhage due to thrombocytopenia. In this study with small sample size, HD rIL-2 and IPI were safe to administer sequentially in MM patients and showed more than additive effects. 1-year OS was superior to that of IPI alone from historical studies.